Strongyloides stercoralis and immunosuppression in dermatology - Diogo Mendes Pedro; João Borges- (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Dermatologists can take advantage of numerous immunosuppressive drugs to treat several conditions such as autoimmune bullous dermatoses, psoriasis, and connective tissue diseases. In particular, corticosteroids often play an important role in the management of these diseases. However, prior to the start of immunosuppressive therapy, screening for opportunistic infections is crucial. Strongyloidiasis is one such disease. The parasite Strongyloides stercoralis is a nematode with a complex life cycle and the ability to autoinfect its host. Although it currently is a rare disease in Portugal, it has a widespread distribution especially amongst low-income countries. It is usually responsible for a chronic asymptomatic infection, albeit frequently with intermittent eosinophilia. Certain comorbidities may increase the risk for hyperinfection or disseminated disease. Such factors are the presence of immunocompromising conditions such as haematological malignancies, AIDS, HTLV-1 infection and therapies such as transplantation and corticosteroids. The screening and diagnosis are usually performed with parasitological and serological tests, and the treatment of choice is ivermectin. As such, since chronic infection can be asymptomatic and hyperinfection potentially lethal, screening prior to the start of immunosuppressive treatment is imperative. Dermatologists that prescribe such regimens should be familiar with the need of parasite screening and management prior to the start of therapy.